TECHNOLOGY OF FUTURE PEDIATRICIANS’ PREPARATION TO WORK IN A TEAM BY MEANS OF INTERACTIVE TEACHING METHODS - Karpova Maryna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article analyzes the essence of the concept of “readiness of future pediatricians to work in a team.” It is proved that one of the factors that contribute to the effective development of the educational process of a modern higher education institution is the preparation of future pediatricians to work in a team. It is determined that the result of training future pediatricians is the formed readiness to work in a team, the components of which are motivational-value, cognitive, operational-activity and personal components. To test the formation of the readiness of future pediatricians to work in a team by means of interactive teaching methods according to certain criteria (motivational-value, cognitive, operationalactivity, personal), research methods are described. The results of testing and survey gave grounds to state mainly the average and low level of readiness of future pediatricians to work in a team. Based on the obtained results, the technology of training future pediatricians to work in a team by means of interactive teaching methods is theoretically substantiated and developed, which is implemented through the following stages: conceptual, professional-motivational, content-activity, and diagnostic-effective ones. The conceptual stage of technology includes the general purpose of technology, tasks, methodological approaches, principles of training. The professional and motivational stage of technology involves the formation of undergraduates’ personal sense of teamwork; needs for communication and interpersonal interaction; motives for self-improvement of one’s own level of readiness to work in a team. The contentactivity stage of the technology is aimed at transforming the content of the educational process in the direction of providing undergraduates with knowledge and skills of teamwork. The diagnostic and effective stage of technology involves control, self-analysis, correction of shortcomings in the development of the studied readiness; diagnosis of the final level of readiness of future pediatricians to work in a team. The ex- The experimental implementation of the developed technology indicates the positive results of the formation of future pediatricians’ readiness to work in a team by means of interactive teaching methods